(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
Modelling based on Computational Fluid Dynamics (CFD) is by now effectively used in fire research and hazard analysis. Depending on the scenario, radiative heat transfer can play a very important role in enclosure combustion events such as tunnel fires. In this work, the importance of radiation and the effect of the use of different approaches to account for it were assessed. Firstly, small-scale tunnel fire simulations were performed and the results compared with experimental data, then realistic full-scale scenarios were simulated. The results show up the capability of CFD modelling to reproduce with good approximation tunnel fires. Radiation proved to be noteworthy mainly when the scale of the fire is relatively large. Among the various approaches employed to simulate radiation, the use of the Discrete Transfer model gave the most accurate results, mainly when the absorption-emission characteristics of the combustion products were taken into account. Finally, the suitability of the use of CFD in quantitative Fire Hazard Analysis is discussed.